2021
DOI: 10.1051/e3sconf/202127502054
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition and Decoupling Analysis of Industrial Solid Waste in the Yangtze River Economic Belt

Abstract: In this paper, LMDI method is used to analyze the driving factors of industrial solid waste production in the Yangtze River Economic Belt from 2005 to 2018, and the decoupling state is analyzed by Tapio indicator. We found that:①Industrial pollution intensity effect and industrial structure effect inhibited industrial solid waste production, while regional output effect and population size effect played a role in increasing the pollution; ②in different periods, the decoupling states of industrial solid waste i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Madden et al (2019) explored regional variation in the decoupling of waste generation from mean income in Australia, following the waste Kuznet’s curve hypothesis. Teli (2021) analysed the driving factors of industrial solid waste generation in the Yangtze River Economic Belt from 2005 to 2018 and found that regional output effect and population size effect played a role in increasing the pollution. Zhang et al (2021) analysed the socioeconomic drivers and identified the key supply chains that cause industrial solid waste generation changes using monetary input-output tables in China.…”
Section: Methodology and Datamentioning
confidence: 99%
“…Madden et al (2019) explored regional variation in the decoupling of waste generation from mean income in Australia, following the waste Kuznet’s curve hypothesis. Teli (2021) analysed the driving factors of industrial solid waste generation in the Yangtze River Economic Belt from 2005 to 2018 and found that regional output effect and population size effect played a role in increasing the pollution. Zhang et al (2021) analysed the socioeconomic drivers and identified the key supply chains that cause industrial solid waste generation changes using monetary input-output tables in China.…”
Section: Methodology and Datamentioning
confidence: 99%
“…The utilization of industrial land resources is often wasted because of irrational land use structures and low utilization efficiency, resulting in environmental degradation and additional land use for industry [28]. In addition, industrialization also produces substantial amounts of environmentally harmful waste [29]. Industrialization is a vast organization of systems that involves the transportation, mining, manufacturing, and management of industrial wastes [30,31].…”
Section: Determinants Of Ecological Footprintmentioning
confidence: 99%